Influence of Eco-Friendly Packaging on Customer Loyalty in Japan - Takahashi, Kaori (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to analyze the influence of eco-friendly packaging on customer loyalty in Japan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on the influence of eco-friendly packaging on customer loyalty in Japan reveals that consumers are increasingly valuing sustainability in their purchasing decisions. Studies show that environmentally conscious packaging enhances brand perception, with Japanese consumers viewing companies that use eco-friendly packaging as socially responsible and ethical. This positive brand association significantly boosts customer loyalty, as many consumers are willing to pay more for products packaged sustainably. Additionally, younger consumers in Japan, particularly Millennials and Gen Z, prioritize eco-friendly packaging, linking it to their personal values of environmental responsibility. Unique Contribution to Theory, Practice and Policy: Theory of planned behavior (TPB), uses and gratifications theory (UGT) & social influence theory may be used to anchor future studies on the influence of eco-friendly packaging on customer loyalty in Japan. Eco-friendly packaging can be an essential differentiator for brands in Japan, where environmental consciousness is culturally significant. Policymakers should consider incentivizing the adoption of eco-friendly packaging through tax breaks or subsidies, which would encourage more brands to switch to sustainable packaging solutions.